Analysis of Culinary Preferences on Customer Satisfaction: Study of Kampung Solor Pasar Malam Culinary Tourism in Kupang City - Ariance Ana Lasibey; Christina Mariana Mantolas; Veronika A. S. M Flora; Elsadian Taimenas; Nova Yunike Ndolu (NHI HOSPITALITY INTERNATIONAL JOURNAL, 2025)
Purpose of the study: This study aims to examine the relationship between culinary preferences and customer satisfaction at Kampung Solor Night Market in Kupang City, East Nusa Tenggara. Design/methodology: The study employs a mixed-method approach, integrating quantitative and qualitative data collection and analysis. A structured questionnaire was administered to 100 respondents selected through accidental sampling. Data were analyzed using SPSS25 for validity and reliability testing, followed by descriptive statistics, correlation analysis, and regression analysis to assess the impact of culinary preferences on customer satisfaction. A case study methodology was also applied to contextualize the findings within the specific setting of Kampung Solor Night Market. Findings: The results reveal a moderate positive relationship between culinary preferences and customer satisfaction, the variation in customer satisfaction is explained by culinary preferences, while the remaining 30.6% is influenced by other factors such as price, food quality, tangibles, branding, and service quality. Among these, food quality had the largest impact on satisfaction (15%), followed by price (10%), with tangibles, branding, and service quality each contributing 5%. External factors, including weather and visitor mood, account for the remaining variations. Research limitations/implications: This study offers valuable insights for tourism management and culinary tourism development in Kupang City, particularly for Kampung Solor Night Market. The findings are relevant to disciplines such as hospitality management, consumer behavior, and tourism marketing. However, the study is limited by its focus on a single location, which restricts the generalizability of the results. Future research should consider comparative studies across different regions to enhance the applicability of the findings. Novelty/Originality of the study: This study uniquely bridges culinary preferences and customer satisfaction within the specific context of Kampung Solor Night Market in Kupang City. By quantitatively and qualitatively analyzing demographic and psychological factors, it offers fresh insights into how these elements drive satisfaction in culinary tourism, thereby advancing knowledge in customer-centric tourism management and culinary experience enhancement.